Materials Pertaining to the Life and Works of Mikhail Gorlin from the Archive of the Institut d’études slaves. Part 3 (No 7: ‘Only Shadows’: Encounters with Marina Tsvetaeva). - Poljakov, Fedor (Literatūra, 2025)
The publication features some of the heretofore unknown materials on the history of Russian literature in exile from the archive of the Institut d’études slaves (Paris). The materials were drawn from Mikhail Gorlin’s (1909–1942) personal archive. M. Gorlin, a poet, a scholar, and an employee of the Institute who had been working there until the repressions following the occupation of France in 1940. These repressions eventually led to his to his murder in the Auschwitz Concentration Camp. The article presents some documents shedding light on Mikhail Gorlin’s encounters with Marina Tsvetaeva (1892–1941), including a previously unpublished draft of Mikhail Gorlin’s letter, in which he explains to Marina Tsvetaeva the eminent Slavist and poet Alexander Vostokov’s treatment of enjambements.
Keywords: 20th-century Russian literature; Mikhail Gorlin; Marina Tsvetaeva; Russian verse; correspondence